A high-voltage solar rechargeable device based on a CoPi/BiVO4 faradaic junction. Issue 4 (5th January 2022) - Zhang, Junzhe; Jiang, Dongjian; Wang, Pin; Zhong, Jun; Sun, Gengzhi; Yao, Yingfang; Luo, Wenjun; Zou, Zhigang
Abstract : CoPi is used as an energy storage material in a two-electrode solar rechargeable device for the first time, which exhibits the highest working voltage among all previously reported devices. Abstract : A two-electrode solar rechargeable device is a potential low-cost method for solar energy conversion and storage. However, a low working voltage limits its practical application. It is significant to develop a solar rechargeable device with a high voltage. Herein, we report a device of BiVO4 /CoPi/KPi(aq) /C with a working voltage of about 0.9 V, which is the highest value among all previously reported two-electrode devices. The high voltage comes from the positive onset potential of CoPi, which is used as the energy storage material for the first time. Moreover, we also investigate the reasons for the positive onset potential of CoPi by comparing with other conventional Co-based materials. The results suggest that CoPi has fewer tetrahedral Co(ii ), which leads to higher oxidation potential than the materials with more octahedral Co(ii ). This study highlights the importance of choosing energy storage materials with suitable potential windows in a solar rechargeable device and offers guidance to improve the performance.